Gāzargāh qismatī az tārīkh-i Hērat-i bāstān - Saljuqī, Fikrī (Da Maṭbūʻāto Mustaqil Riyāsat, da Korinayo Khparawano Loy Mudīrīyat, 1962)
Historical description of the burial ground of Afghan religious leader ʻAbd Allāh ibn Muḥammad Anṣārī al-Haravī, 1006-1089, and other Afghan elite buried in its vicinity.